Estratégias de argumentação em textos de alunos do Projeto Educação Aberta (PREA) - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
This thesis, within the scope of languages and social practices, aims to analyze the process by which PrEA students construct argumentation in their writing. To that end, the use of argumentative operators, verb tenses and modalizing clauses was observed. The PrEA (Open Education Project) - is an extension project created and led by volunteers who coordinate and administer preparatory classes for university entrance exams, from Monday to Saturday, in the UEG - UnUCSEH (State University of Goiás - Socioeconomic and Social Sciences Unit) building. All students enrolled in the project come from public high schools. In 2014, classes and after-class writing help were monitored to compose this thesis. The monitoring of the project's routine was done through observation and taking notes on points that were relevant to the research. The proposed topics for writing production provided by the writing teacher, as well as the argumentative texts produced during the second semester of 2014 were copied and saved for analysis. Six essays, written on two different topics (three from each topic), were chosen. For the analysis of the argumentative texts, in this paper, the concepts addressed included genre, language, context, text, in addition to theory on argumentative genre, argumentation and academic writing production. Through this qualitative ethnographic research, and analysis, it was noted that students do not demonstrate great skill in consciously dealing with argumentative operators to compose texts. Some texts do not contain modalizing clauses that serve to strengthen the argument put forward by the student or that promote the reader’s involvement with the text. The use of verb tenses in the argumentative texts focuses more on commentary, which demonstrates greater engagement on the author’s part and is full of responsive attitude. It was determined, therefore, that the Open Education Project students, from public schools, do not demonstrate proficiency in the use of argumentation strategies to compose a consistent text design.
Keywords: Argumentação; Gênero textual; Operadores argumentativos; Produção de texto; PREA - Universidade Estadual de Goiás; Argumentation; Textual genre; Writing composition; Argumentative operators; LETRAS::LINGUA PORTUGUESA; CIENCIAS HUMANAS::EDUCACAO